THE EFFECT OF WORK STRESS AND INDIVIDUAL CHARACTERISTICS ON EMPLOYEE PERFORMANCE AT PT MITRA AGRO SERVINDO MEDAN - Ahmad Reezky Ananda; Nur Aisyah; Sjahrir Effendy (RADJA PUBLIKA, 2023)
This research get the result thatthat if the variable work stress (X1) and individual characteristics (X2) simultaneously have a value of zero, then employee performance (Y) will have a value of 17.226, if work stress variable (X1) increases by one unit, then employee performance (Y ) will increase by 0.432 units and if the individual characteristic variable (X2) increases by one unit, then employee performance (Y) will increase by 0.178 units. The Job Stress variable has a tcount of -0.798. This value is smaller than the ttable value (-0.798 <1.659) with a Sig. which is greater than 0.05 (0.432 > 0.05). This shows that partially, work stress variable does not have a significant effect on the performance of employees of PT Mitra Agro Servindo. The Individual Characteristics variable has a tcount of 1.384. This value is smaller than the ttable value (1.384 > 1.659) and is positive with a Sig value. which is smaller than 0.178 (0.021 > 0.05). This shows that partially, individual characteristic variables do not have a significant effect on the performance of employees of PT Mitra Agro Servindo. These results indicate that the variables of job stress and individual characteristics have an influence of 9.3% on the performance of employees of PT Mitra Agro Servindo while the remaining 90.7% is explained by other variables not examined in this study. individual characteristic variables do not have a significant effect on the performance of employees of PT Mitra Agro Servindo. These results indicate that the variables of job stress and individual characteristics have an influence of 9.3% on the performance of employees of PT Mitra Agro Servindo while the remaining 90.7% is explained by other variables not examined in this study. individual characteristic variables do not have a significant effect on the performance of employees of PT Mitra Agro Servindo. These results indicate that the variables of job stress and individual characteristics have an influence of 9.3% on the performance of employees of PT Mitra Agro Servindo while the remaining 90.7% is explained by other variables not examined in this study.